Ornithine Lipids in Burkholderia spp. Pathogenicity - Córdoba-Castro, Luz América; Salgado-Morales, Rosalba; Torres, Martha; Martínez-Aguilar, Lourdes; Lozano, Luis; Vences-Guzmán, Miguel Ángel; Guan, Ziqiang; Dantán-González, Edgar; Serrano, Mario; Sohlenkamp, Christian (Frontiers in Molecular Biosciences, 2021)
The genus Burkholderia sensu lato is composed of a diverse and metabolically versatile group of bacterial species. One characteristic thought to be unique for the genus Burkholderia is the presence of two forms each (with and without 2-hydroxylation) of the membrane lipids phosphatidylethanolamine (PE) and ornithine lipids (OLs). Here, we show that only Burkholderia sensu stricto strains constitutively form OLs, whereas all other analyzed strains belonging to the Burkholderia sensu lato group constitutively form the two forms of PE, but no OLs. We selected two model bacteria to study the function of OL in Burkholderia sensu lato: (1) Burkholderia cenocepacia wild-type which constitutively forms OLs and its mutant deficient in the formation of OLs and (2) Robbsia andropogonis (formerly Burkholderia andropogonis) which does not form OL constitutively, and a derived strain constitutively forming OLs. Both were characterized under free-living conditions and during pathogenic interactions with their respective hosts. The absence of OLs in B. cenocepacia slightly affected bacterial growth under specific abiotic stress conditions such as high temperature and low pH. B. cenocepacia lacking OLs caused lower mortality in Galleria mellonella larvae while R. andropogonis constitutively forming OLs triggers an increased formation of reactive oxygen species immediately after infection of maize leaves, suggesting that OLs can have an important role during the activation of the innate immune response of eukaryotes.